Association of vitamin B12, folate, and homocysteine with COVID-19 severity and mortality: A systematic review and meta-analysis - Ulloque-Badaracco, Juan R. (2024)
Objective: We aimed to review the available evidence on the association between vitamin B12, folate, and homocysteine levels with worse outcomes among COVID-19 patients. Methods: The search was carried out in ten databases simultaneously run on 10 May 2023, without language restrictions. We included cross-sectional, case-control, and cohort studies. The random-effects meta-analysis was performed using the Sidik-Jonkman method and corrected 95% confidence intervals using the truncated Knapp-Hartung standard errors. Standardized mean difference and 95% CI was used as the measure effect size. Results: Thirteen articles were included in this review (n = 2134). Patients with COVID-19 who did not survive had the highest serum vitamin B12 values (SMD: 1.05; 95% CI: 0.31–1.78; p = 0.01, I2 = 91.22%). In contrast, low serum folate values were associated with patients with severe COVID-19 (SMD: −0.77; 95% CI: −1.35 to −0.19; p = 0.02, I2 = 59.09%). The remaining tested differences did not yield significant results. Conclusion: Elevated serum levels of vitamin B12 were associated with higher mortality in patients with COVID-19. Severe cases of COVID-19 were associated with low serum folate levels. Future studies should incorporate a larger sample size.